Penile metastasis of prostatic adenocarcinoma: Report of two cases and review of literature - Philip, Joe (BioMed Central, 2003)
BACKGROUND: Carcinoma of the prostate metastasising to the penis is rare. These patients have a poor prognosis receiving various treatment modalities. CASE PRESENTATION: Two such patients are discussed here having received differing therapeutic regimes, pointing out the necessity for standardised palliative treatment rather than radical therapy. CONCLUSION: Management of patients with penile metastases from carcinoma of the prostate should emphasise improving quality of life with palliative treatment rather than radical therapy